O vermelho e o negro: intolerância, construção da identidade nacional e práticas educativas durante o estado novo (1937 1945) - Felipe Menezes Pinto (2011)
This work aims to conduct a study of the relationship between the state of Vargas from 1937 to 1945, a political period known as New State, and the educational practices concerned in this period. These practices, ed ucational related ornot, seemed to have promoted Vargas ideological propaganda and to have built a (new) collective national identity. Over the mediations involved in this process of identity construction (rooted in values such as the exaltation of our homeland, nation, family andwork), we can observe manifestations of intolerance, exposing, in fact, relations with the wider context of the era, notably marked by rise of authoritarian regimes founded on the exclusion of some ethnic, religious and political groups. I am interested in how these ideas of intolerance which is recorded in the authoritative discourse were present in theeducational universe experienced by children, particularly in school and after-school supplies, both in textbooks and teaching materials in general as well as in childrens supplements in the Minas Gerais newspapers of the time. By analyzing the authoritative discourse during the New State of Vargas and its manifestations of intolerance, especially those that aim to target the school public throughout school materials such as booklets, I will restrict my view particularly in two groups, namely, the Communists and Blacks. The authoritative discourse, besides to conform the nation in what would be their identity, what it would be proper and essential, also intended to inculcate with what would be stodgy, unhealthy and undesirable. Within these practices and discourses of disqualifying otherness, the school would appear as a place of excellence where the actions of this "sanitary pedagogy" and of this alleged racial purification will develop, a place where the discourse of One Harmonic Brazilian Nation is present and, therefore, a place for intolerance to certain groups.To that extent, as the object of analysis favored the teaching materials for children at the time of the Estado Novo, the central concern of this dissertation will be the pursuit of the path taken in building practices and intolerant discourses through these materials, the symbolic elements involved in this warp, the constructed representations of reality with the children, as well as possible traces of reading, possible that these appropriations were intolerant of this discourse in which they were immersed